Multipoint formulas for scattered far field in multidimensions. (31st August 2020) - Novikov, R G
Abstract: We give asymptotic formulas for finding the scattering amplitude at fixed frequency and angles (scattered far field) from the scattering wave function given at n points in dimension d ⩾ 2. These formulas are explicit and their precision is proportional to n . To our knowledge these formulas are new for n ⩾ 2; whereas they reduce to a classical result for n = 1.